The Relation of Ūlul Ilmi, Ūlul Albāb, and Ūli an-Nuha Term in Forming The Whole Human Being Concept - Nurti Budiyanti; Aan Hasanah; Muhibbin Syah; Andewi Suhartini (AL-ISHLAH: Jurnal Pendidikan, 2022)
Education is a process of coaching and developing human potential optimally that reaches whole aspect of life dimension, including soul, intelligence, and heart that construct human personality. But, the reality, education nowadays is still focusing on vocational aspect, while their personality is still neglected. Thus, the targeted purpose was only partial not thoroughly. This condition was not aligned with the purpose of education that should be normative and integrative so that the direction aimed was in accordance with the idea of expected ideal human qualification based on Koran soul in the entire life aspect stated by some educational practitioners. Therefore, this research was aimed at describing the involvement of whole life aspect in shaping a whole human being which was built from Ūlul Ilmi, Ūlūl Albāb and Ūli an-Nuha terms to formulate the purpose of Islamic education. This reasearch applied qualitative approach along with tahlīlī and muqāran as the procedural methods regarding to the ten Mu’tabaroħ tafsirs; they were Al-Miṣbāḥ Tafsir, Fi Ẓilalil Qur`ān Tafsir, Ibn Kaṡīr Tafsir, Aṭ-Ṭabari Tafsir, Al-Qurṭubi Tafsir, Al-Maraghi Tafsir, Al-Mizan Tafsir, Al-Azhar Tafsir, At-Taḥrir Wa Tanwir Tafsir and Fakr Ar-Razi Tafsir. Also, literature study was applied to collect the data. The data analysis technique used in this study was text analysis which employed dilālaħ and munāsabaḥ. According to the findings and analysis in this study, it was stated that the purpose of whole human being an intelectual thinker who is pious and brilliant, knowledgeable, sharp minded, pure heart, pertinacious beliefs, strong istinbath, noble soul, great moral character, and has an absolute spiritual experience. The central implication from the whole human being concept lied on the purpose of Islamic education with Ilāhiyyah nuance, divine and spiritual. Other educative implications are role, function, principle, educator, student, method, material, and teaching media. All those educational components were directed to strengthen beliefs, straighten worship, and devoted akhlakul karimah to be ma’rifatullāh.